2009
DOI: 10.1371/journal.pone.0005822
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of eDNA Release and Degradation Affects Staphylococcus aureus Biofilm Maturation

Abstract: Recent studies have demonstrated a role for Staphylococcus aureus cidA-mediated cell lysis and genomic DNA release in biofilm adherence. The current study extends these findings by examining both temporal and additional genetic factors involved in the control of genomic DNA release and degradation during biofilm maturation. Cell lysis and DNA release were found to be critical for biofilm attachment during the initial stages of development and the released DNA (eDNA) remained an important matrix component durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
441
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(475 citation statements)
references
References 50 publications
22
441
4
2
Order By: Relevance
“…It is possible that enzymes that degrade biofilm polymers provide additional structuring for which there is some recent evidence in S. aureus (7,8); however, how such enzymes contribute to biofilm maturation awaits in-depth investigation. Furthermore, our study suggests that targeting biofilm-structuring surfactant molecules might represent a promising approach to prevent the formation of viable medical and environmental biofilms, although the species-specific chemical nature of these molecules would likely require a specific form of interference in every case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that enzymes that degrade biofilm polymers provide additional structuring for which there is some recent evidence in S. aureus (7,8); however, how such enzymes contribute to biofilm maturation awaits in-depth investigation. Furthermore, our study suggests that targeting biofilm-structuring surfactant molecules might represent a promising approach to prevent the formation of viable medical and environmental biofilms, although the species-specific chemical nature of these molecules would likely require a specific form of interference in every case.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes that degrade essential biofilm polymers may theoretically contribute to biofilm detachment; however, there is only preliminary evidence for such enzyme function in S. aureus or other staphylococci (7,8). In contrast, there are reports indicating that several bacteria use surfactant-like molecules to structure and detach biofilms, which include Bacillus subtilis surfactin (9, 10), Pseudomonas aeruginosa rhamnolipid (11,12), and the phenolsoluble modulin (PSM) ÎČ-peptides in Staphylococcus epidermidis, a close relative of S. aureus (4).…”
mentioning
confidence: 99%
“…Cells of the pooled mutant library were grown under biofilm-inducing conditions, and biofilms were harvested at 6 and 8 h. Preliminary studies had indicated that eDNA release is at its peak during this window (12). Because of the potential risk of population bottlenecks stemming from varying representation of the mutant library in different experiments, the experiment was repeated at both time points.…”
Section: Identification Of Transposon Insertions In Genes Underrepresmentioning
confidence: 99%
“…Other factors implicated in cell lysis are toxin/antitoxin system that have been characterized, for example, in Enterococcus faecalis (Thomas et al, 2008) and Staphylococcus sp. (Qin et al, 2007;Rice et al, 2007;Mann et al, 2009). However, a role for toxin/antitoxin systems in biofilm formation is not necessarily directly linked to cell lysis, as has been demonstrated for E. coli (Kim et al, , 2010.…”
Section: Mutants Lacking the Prophages Are Defective In Biofilm Formamentioning
confidence: 99%
“…In contrast, the significance of eDNA for cellular attachment and structural integrity has more recently been recognized for an increasing number of Gram-negative and Grampositive species (Whitchurch et al, 2002;Steinberger and Holden, 2005;Allesen-Holm et al, 2006;Moscoso et al, 2006;Jurcisek and Bakaletz, 2007;Qin et al, 2007;Izano et al, 2008;Thomas et al, 2008;Heijstra et al, 2009;Vilain et al, 2009;Harmsen et al, 2010;Lappann et al, 2010). Release of DNA in bacterial biofilms has mainly been attributed to the lysis of a cellular subpopulation, mediated by the activity of autolysis systems (Allesen-Holm et al, 2006;Rice et al, 2007;Thomas et al, 2008Thomas et al, , 2009Mann et al, 2009). The analysis of aggregates formed by S. oneidensis MR-1 in planktonic cultures indicated the presence of proteins, a-D-mannose or a-D-glucose containing exopolysaccharides, and substantial amounts of eDNA (McLean et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%